Long Before Aï-Khanoum: Historiographical Representation of Hellenistic Bactria In Barthold Niebur's Vötrage Über Alte Geschichte (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2019)
This paper deals with the historiographical representation of Hellenistic Bactria in Barthold Niebuhr’s Lectures on Ancient History, based on lectures given at Bonn University in the 1820’s and published in German and English in the 1850’s. The first part offers a panorama of archaeological, epigraphic and numismatic research after the great French excavations in Afghanistan in the 1960 and 1970’s. The second part discusses how Niebuhr, facing a poorly documented Bactrian history and archaeology, articulate source criticism, demographic, moral and racial reasoning and contemporary political debate. The paper concludes with a summary of the discussion, arguing for the necessity of historicization of historiographicalsyntheses as well in nineteenth century as today, especially in the context of Global History.